Experimental study on bending and shear behaviours of composite timber sandwich panels. (30th October 2020) - Darzi, Siavash; Karampour, Hassan; Bailleres, Henri; Gilbert, Benoit P.; McGavin, Robert L.
Highlights: Sandwich panels with plywood skins and bamboo/peeler core rings were manufactured. The manufactured panels were tested in four-point bending and three-point shear tests. Results were compared to the test results of CLT. Results suggest that the proposed sandwich panels can be a potential alternative for CLT in terms of structural performance. Abstract: Composite sandwich panels were manufactured by gluing plywood skins to either bamboo rings to produce Bamboo Core Sandwich (BCS) panels or to peeler core rings to produce Peeler Core Sandwich (PCS) panels. Single and double core layer panels were made. The optimum adhesive spread rate was identified through conducting shear bond tests. The manufactured panels were physically tested in standard bending (using four-point) and shear (using three-point) tests. Results were compared to the test results of conventional Cross-laminated Timber (CLT) panels with almost similar depth. Under bending action, both the BCS and PCS panels showed tensile failure in the plywood, while the plywood in compression exceeded its plastic limit at the ultimate load. In shear, BCS panels failed due to the loss of shear interface contact between bamboo core rings and the plywood skins, whereas PCS panels showed local indentation/bond failure between the peeler core rings and the plywood skins. No significant improvements were observed in the double-layer panels compared to single-layer panels in bending. However, in shear, double-layer panels showed more consistent capacities. One PCS panel with thicker plywood skins and less peeler core rings (PCS-TH) was manufactured, and was shown to achieve 0.77 times the bending stiffness-to-weight ratio of the commercial CLT panel. Reduced weight, lower material costs, ease of manufacturing and usage of sustainable/waste products, make the proposed sandwich panels a potential alternative for CLT in terms of structural performance. Moreover, the proposed peeler core sandwich panels displayed better ductile performances in bending and shear compared to CLT suggesting it could be a preferred product choice in some building applications.